Resiliencia y Rendimiento Escolar en Adolescentes de Lima y de Santiago de Chile de Sectores Vulnerables [Resilience and Academic Performance of Lima and Santiago de Chile Adolescents from Vulnerable Social Level] - Villalta-Paucar, M (Pontificia Universidad Javeriana, 2017)
The aim of the study is to propose measuring instruments resilience related to school performance valid for adolescents from vulnerable social groups in urban areas of two South American countries. The research method is based on analysis of the statistical results of the items and dimensions of the resilience of the SV-RES Scale in 764 adolescents from vulnerable urban areas of Lima, Peru and 1,145 from Santiago de Chile with high and low academic performance of sectors with social vulnerability. Exploratory Factor Analysis (AFE), convergent and discriminant validity analysis was performed. The results suggest new different dimensions of resilience linked to academic performance on adolescents of Lima and Santiago de Chile.